Species Diversity of Lichens in Curug Sadim, Sagalaherang District, Subang, West Java - Susanto, Hawa Hafifah Putri; Khalidazia, Khaila; Septiano, Fadlan; Husin, Husin; Gumelar, Indra Surya; Falah, Nazwa Rakhma; Amalia, Fauziah Husna; Irawan, Afri (Universitas Pendidikan Indonesia and Konsorsium Biologi Indonesia, 2025)
Despite its ecological significance, including its function as a sink for pollutants, a provider of oxygen, and a bioindicator of air quality, a comprehensive study of lichen diversity in Subang, West Java, has not been conducted. The objective of this study is to analyze the diversity of lichen found in the Curug Sadim natural tourism area, Subang. Data collection was carried out through the implementation of the cruising method at three observation stations. The results of this study indicated the presence of ten lichen species, classified into eight families, Namely Caloplaca sp. (Teloschistaceae), Cladonia sp. (Cladoniaceae), Cryptothecia scripta (Arthoniaceae), Cryptothecia striata (Arthoniaceae), Dirinaria sp. (Caliciaceae), Flavoparmelia caperata (Parmeliaceae), Graphis scripta (Graphidaceae), Leptogium cyanescens (Collemataceae), Parmotrema hypotropum (Parmeliaceae), and Phlyctis sp. (Phlyctidaceae). These lichen species are found attached to substrates such as trees and rocks, and they exhibit various thalus types, including fruticose, crustose, and foliose. The presence of lichen with high variation indicates that the environment of Curug Sadim is relatively clean and supports the survival of bioindicator organisms. These findings are of significant importance in light of their contribution to our understanding of local biodiversity and the potential of lichen as a bioecological indicator in monitoring environmental quality.